EMR + with the AWC improves endoscopic resection speed compared to ESD: a porcine ex-vivo pilot study. Issue 1 (1st February 2021) - Wedi, Edris; Knoop, Richard; Jung, Carlo; Gromski, Mark; Ho, Chi Nghia; Conrad, Gabor; Maiss, Juergen; Milenovic, Sinisa; Klemme, David; Baulain, Ulrich; Seif Amir Hosseini, Ali; Ellenrieder, Volker; et al.
Abstract: Introduction: To improve resection speed and to reach higher en bloc resection rates in lesions ≥ 2 cm, a novel grasp and snare EMR technique termed "EMR+", accomplished by an additional working channel (AWC), was developed. Its use compared to endoscopic submucosal dissection (ESD) is evaluated for the first time. Material and methods: We prospectively conducted a randomized pre-clinical ex-vivo pilot study in explanted porcine stomachs for the comparison of EMR + with classical ESD of mucosal-based lesions. Prior to intervention, we set flat lesions with a standardized size of 3 × 3 cm. Results: The median time of procedure was significantly shorter in the EMR + group (median 10.5 min, range 4.4–24 min) than in the ESD group (median 32 min, range 14–61.6 min, p  < .0001). The rate of en bloc resection was significantly lower in the EMR + group (38 % vs. 95 %) ( p  < .0001). Nevertheless, an improvement in the learning curve for EMR + was achieved after the first 12 procedures, with a subsequent en bloc resection rate of 100 %. Conclusions: EMR + could improve the efficiency of mucosal resection procedures. Initial experience demonstrates a higher and satisfactory en bloc resection rate after going through the learning curve of EMR+.